A Case of Diabetic Ketoacidosis in a Patient on an SGLT2 Inhibitor and a Ketogenic Diet: A Critical Trio Not to Be Missed - Samantha Steinmetz-Wood; Matthew Gilbert; Katherine Menson (Case Reports in Endocrinology)
Results from major clinical trials have shown significant cardiorenal-protective benefits of SGLT2 inhibitors in patients with type 2 diabetes (T2DM), leading to increased popularity. A rare but serious side effect of SGLT2 inhibitors is euglycemic diabetic ketoacidosis (EDKA), which presents more covertly but has been described. Identification and report of modifiable risk factors would be an important step in helping clinicians appropriately counsel patients. In this case report, we present DKA in a patient on an SGLT2 inhibitor and ketogenic diet (KD). A 47-year-old male with a history of poorly controlled T2DM on metformin and empagliflozin presented to the emergency department (ED) with several days of pharyngitis, dyspnea, emesis, abdominal pain, and anorexia. Of note, one month prior to this event, he presented to the ED with malaise and was found to have an anion gap of 21, a bicarbonate level of 13 mmol/L, a pH level of 7.22, 3+ ketonuria, and a glucose level of 7 mmol/L (127 mg/dl). Additional workup was negative, and findings were attributed to his KD. His use of empagliflozin was not identified on his medication list. At second presentation, the patient was tachypneic and tachycardic and had mild abdominal tenderness. Labs revealed anion gap 28, bicarbonate 5 mmol/l, pH 6.94, 3+ ketonuria, glucose 14.9 mmol/L (269 mg/dl), and beta-hydroxybutyrate 8.9 mmol/L. The patient was diagnosed with DKA and was treated accordingly. With closure of anion gap, the patient was transitioned to insulin and metformin, and his empagliflozin was discontinued indefinitely. Before prescribing this medication class, physicians should inquire about low-carbohydrate diets given the higher risk for DKA, though knowledge of this risk is still not widespread.